Prediction of biological activity of spiroquinazolone derivatives as protein kinase inhibitors FGFR1 and CK2 - O. K. Farat; S. A. Varenychenko; V. I. Markov (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
The purpose. The search for FGFR1 and CK2 protein kinase inhibitors were performed among spiroquinazolone derivatives using receptor-oriented virtual screening and in vitro biochemical testing using the human CK2 kinase domain.